The incarnate Logos and manunggaling kawulo Gusti: Theosis in Javanese Christian spirituality - Tri Astuti; Joko Priyono (Institut Agama Kristen Negeri Toraja, 2026)
This study investigates the concept of Manunggaling Kawulo Gusti within Javanese spirituality, employing a theological framework centered on the incarnation of the Logos, with a focus on the soteriological doctrine of Theosis and on intercultural hermeneutics as conceptualized by Paul Ricoeur. Employing a qualitative critical literature review methodology, this research brings primary theological sources, biblical exegesis, and Javanese cultural anthropology into the critical dialogue. The analysis demonstrates that Manunggaling Kawulo Gusti articulates a profound Javanese aspiration toward ontological union with the Divine, expressed through ascetic practice (laku), contemplative silence (suwung), and cosmic harmony (memayu hayuning bawana). This research suggests that the idea of the Logos incarnate, understood as the union of God and humanity in the person of Christ, provides a standard framework for re-examining Javanese spiritual aspirations. The study proposes Theosis as a conceptual link, rather than categorizing Manunggaling Kawulo Gusti as syncretism or assimilating it into an evangelical context, suggesting that the movement of the Logos towards humanity (incarnation) facilitates the possibility of humanity’s transformation and participation in the divine life. The role of the Holy Spirit as the agent of both the incarnation and the ongoing process of Christification is foregrounded throughout.